Dila ng bayan - Medina, Isagani R.; National Commission on Culture and the Arts (Philippines). Committee on Language and Translation (Manila National Commission for Culture and the Arts, Committee on Language and Translation, 2005)
On history of Philippine languages and culture.
Includes bibliographical references (p. 81-88) and index.
Library Fees
English and Tagalog.
Keywords: Philippine languages -- History; Language and culture -- Philippines